Analisis Kandungan Protein dan Karakteristik Organoleptik pada Flakes Ampas Tahu sebagai Alternatif Sarapan Sehat - Risna Dwi Kirani; Umar Hidayat; Chairunnisa Nur Rarastiti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
This study aims to determine the effect of tofu pulp flour formulation with the addition of corn flour on protein content and organoleptic characteristics in flakes products. There were 6 treatments in this study with differences in the concentration of tofu pulp flour and corn flour of F0 = 0%: 100%, F1 = 50%: 50%, F2 = 55%: 45%, F3 = 60%: 40%, F4 = 65%: 53%, F5 = 70%: 30%. Protein levels were tested using the kjeldahl method, then the data were analyzed with  the One Way Analysis of Variance (ANOVA) parametric test. The analysis of hedonic organoleptic data used was Kruskall-Wallis with color, aorma, taste and texture parameters. The results of the study showed that the highest protein content was found in the F2 formulation with an average of 4.505%. Organoleptic tests showed that the F2 formulation had the highest level of preference in color, aroma, taste and texture parameters.